Женщины, кот и собака: [сборник] / Мария Метлицкая - Метлицкая Мария (Эксмо, 2023)
Экземпляры: ф.11 (2024) / Инвентарный номер: 60130 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 54 / ББК: 84(2=411.2)6-44